2015
DOI: 10.4155/fmc.15.45
|View full text |Cite
|
Sign up to set email alerts
|

Rho Kinase as a Target for Cerebral Vascular Disorders

Abstract: The development of novel pharmaceutical treatments for disorders of the cerebral vasculature is a serious unmet medical need. These vascular disorders are typified by a disruption in the delicate Rho signaling equilibrium within the blood vessel wall. In particular, Rho kinase overactivation in the smooth muscle and endothelial layers of the vessel wall results in cytoskeletal modifications that lead to reduced vascular integrity and abnormal vascular growth. Rho kinase is thus a promising target for the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 160 publications
(190 reference statements)
0
17
0
Order By: Relevance
“…ROCKs regulate contractility of endothelial cells and SMCs through dephosphorylation of myosin light chain subunits which results in cell relaxation, whereas calcium influx and activation of myosin light chain kinase counter ROCKs by promoting cell contraction (Bond et al . ; Huveneers et al . ).…”
Section: Role Of Rocks: Vascular Pathologies and Vascular Risk Factormentioning
confidence: 97%
“…ROCKs regulate contractility of endothelial cells and SMCs through dephosphorylation of myosin light chain subunits which results in cell relaxation, whereas calcium influx and activation of myosin light chain kinase counter ROCKs by promoting cell contraction (Bond et al . ; Huveneers et al . ).…”
Section: Role Of Rocks: Vascular Pathologies and Vascular Risk Factormentioning
confidence: 97%
“…In blood vessels, the Rho/Rho-associated protein kinase (ROCK) pathway is expressed abundantly in the vascular smooth muscle and is known to regulate vasoreactivity4445. Noteworthy in this context is that this family of proteins is recognized as key signalling molecules that regulate arterial blood pressure and are important mediators involved in maintaining vascular tone in pathophysiological conditions, such as hypertension4647. Hence, any alterations in the hemodynamic balance and level of activation of the Rho protein family members may compromise the vascular integrity and lead to various vasculopathies4348.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, there has been increasing experimental evidence underlining the involvement of two isoforms of ROCK, ROCK1 and ROCK2 in numerous cardiovascular and renal disorders. The activity of this pathway is increased in disorders such as heart failure, coronary artery disease and cerebrovascular disease, all of which associated with tissue hypoxia and reduced integrity of tissue vasculature (18,19,23).…”
Section: Discussionmentioning
confidence: 99%
“…brain, heart etc.) (18,19). In a single study, ROCK activity has been shown to be increased in OSAS in correlation with increased C-reactive protein (CRP) concentration and reduced flow-mediated dilatation in the brachial artery suggesting the presence of an interplay with ROCK and endothelial dysfunction (20).…”
mentioning
confidence: 99%